Clino-pathological features of urinary tract infection: a study at Nishtar University Hospital Multan, Punjab, Pakistan - Mehar, M. Faisal; Safdar, Rabia Saleem; Khan, Afsheen Asghar; Naz, Madiha; Iqbal, Bushra; Nasir, Ali Rehan (International Journal of Research in Medical Sciences, 2020)
Background: Urinary tract infection (UTI) is a common clinical issue among pediatric population and might progress into renal scaring, hypertension as well as end stage kidney disease. This study was aimed at finding clino-pathological features of UTI and antibiotic sensitivity against most common causative agents involved at a tertiary care hospital of South Punjab, Pakistan. Methods: This descriptive case series study was conducted at department of Paediatric Medicine, Nishtar University Hospital Multan from July to December 2019. A total of 100 children fulfilling the inclusion criteria, presenting in outpatient department or emergency section of paediatric medicine department, having positive urine culture and sensitivity were selected. Their detailed history, clinical examination and relevant investigations were done. Results: Out of the 100 children, 73 (73.0%) were female and 27 (27.0%) were male. There were 57 (57.0%) children from 1 year to 4 years age group and 43 (43.0%) were of more than 4 years. Most common clinical presentations were fever 83 (83.0%), urinary symptoms, vomiting 52 (52.0%) and pain abdomen 48 (48.0%). Most common aetiological agents were Escherichia coli 74 (74.0%) and Klebsiella pneumoniae 9 (9.0%). Conclusions: UTI is more common in female children. Most common presentation observed was fever and/or urinary symptoms while most common aetiological agent was E. coli.